Dryland Sunflowers in Western Kansas—Oil Type (W-S-F Rotation) - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on typical production practices of sunflowers in western Kansas.
MF887_1995_10
Keywords: MF887; Economics; Crops; MF